2016
DOI: 10.3390/f7060121
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Changes in Structure for a Mediterranean Urban Forest: Santiago, Chile 2002 to 2014

Abstract: Abstract:There is little information on how urban forest ecosystems in South America and Mediterranean climates change across both space and time. This study statistically and spatially analyzed the spatio-temporal dynamics of Santiago, Chile's urban forest using tree and plot-level data from permanent plots from 2002 to 2014. We found mortality, ingrowth, and tree cover remained stable over the analysis period and similar patterns were observed for basal area (BA) and biomass. However, tree cover increased, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 36 publications
(94 reference statements)
0
23
0
5
Order By: Relevance
“…Furthermore, the most significant dynamics related to urban growth is the loss of vegetation cover around the periphery due to the replacement of natural land cover by impervious surfaces. Nevertheless, several studies have suggested that urban expansion is also attributed to a reduction of vegetation cover in the urban center, because of the steady rise in urban density and paving of green spaces [49,62,63]. In this investigation, the loss of about 45.3% of vegetation cover including natural forest, could contribute to the deterioration of the environmental services of a city.…”
Section: Urbanization and Its Influences On The Landscape Compositionsmentioning
confidence: 76%
“…Furthermore, the most significant dynamics related to urban growth is the loss of vegetation cover around the periphery due to the replacement of natural land cover by impervious surfaces. Nevertheless, several studies have suggested that urban expansion is also attributed to a reduction of vegetation cover in the urban center, because of the steady rise in urban density and paving of green spaces [49,62,63]. In this investigation, the loss of about 45.3% of vegetation cover including natural forest, could contribute to the deterioration of the environmental services of a city.…”
Section: Urbanization and Its Influences On The Landscape Compositionsmentioning
confidence: 76%
“…Resultados significativos con p < 0.05. tanto la cantidad de árboles (Brown, 2012) como su diversidad, área de copa y otros atributos estructurales (Escobedo et al, 2015), son mayores en los estratos más altos. De manera similar, este patrón de mayor abundancia y calidad de la infraestructura verde en las zonas con mejor condición socioeconómica, ha sido observado en otras ciudades de Latinoamérica (De la Maza et al, 2002;Pedlowski et al, 2002;Escobedo et al, 2016), Norteamérica (Schwarz et al, 2015;Nesbitt y Meitner, 2016) y Europa (Kabisch y Haase, 2014). Teniendo en cuenta que los estratos socioeconómicos buscan capturar las diferencias socioeconómicas de la población (Hernández, 2016), los resultados obtenidos indican problemas de inequidad ambiental en Bogotá, tal como han concluido previamente otros autores (Brown, 2012;Escobedo et al, 2015).…”
Section: Discussionunclassified
“…Implementation of forecasting methods [31,32], combined with different tools for trend breaks in time series [33], requires further work. Moreover, to gain better understanding of the spatio-temporal dynamics [34] of forest fires in the area considered here, spatial analysis is necessary over the long term.…”
Section: Discussionmentioning
confidence: 99%